The effect of soy isoflavones supplementation on metabolic status in patients with non-alcoholic fatty liver disease: a randomized placebo controlled clinical trial - Asal Neshatbini Tehrani; Behzad Hatami; Ghazal Daftari; Azita Hekmatdoost; Zahra Yari; Amin Salehpour; Seyed Ahmad Hosseini; Bizhan Helli (BMC, 2024)
Abstract Background Non-alcoholic fatty liver disease (NAFLD) accounts as a crucial health concern with a huge burden on health and economic systems. The aim of this study is to evaluate the effect of soy isoflavones supplementation on metabolic status in patients with NAFLD. Methods In this randomized clinical trial, 50 patients with NAFLD were randomly allocated to either soy isoflavone or placebo groups for 12 weeks. The soy isoflavone group took 100 mg/d soy isoflavone and the placebo group took the similar tablets containing starch. Anthropometric indices, blood lipids, glycemic parameters and blood pressure were measured at the beginning and at the end of the study. Results At the end of week 12 the level of serum triglyceride (TG), low density lipoprotein (LDL) and total cholesterol (TC) was significantly decreased only in soy isoflavone group compared to baseline (P < 0.05). Although waist circumference (WC) decreased significantly in both groups after 12 weeks of intervention (P < 0.05), hip circumference (HC) decreased significantly only in soy isoflavone group (P = 0.001). No significant changes observed regarding high density lipoprotein (HDL) and blood pressure in both groups. At the end of the study, serum glucose level was significantly decreased in the placebo group compared to baseline (P = 0.047). No significant changes demonstrated in the soy isoflavone group in regard to glycemic parameters (P > 0.05). Conclusions This study revealed that soy isoflavones could significantly reduce TG, LDL TC, WC and HC in NAFLD patients. Trial registration The Ethics committee of Ahvaz Jundishapur University of Medical Sciences approved the protocol of the present clinical research (IR.AJUMS.REC.1401.155). The study was in accordance with the Declaration of Helsinki. This study's registered number and date are IRCT20220801055597N1 and 20.09.2022, respectively at https://fa.irct.ir .